26=27+x

Simple and best practice solution for 26=27+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=27+x equation:



26=27+x
We move all terms to the left:
26-(27+x)=0
We add all the numbers together, and all the variables
-(x+27)+26=0
We get rid of parentheses
-x-27+26=0
We add all the numbers together, and all the variables
-1x-1=0
We move all terms containing x to the left, all other terms to the right
-x=1
x=1/-1
x=-1

You can always share this solution

See similar equations:

| 2v+6=4(v-2) | | 25+30+x=90 | | x+5÷4=3 | | -3(y-6)=-7y+14 | | 4(u-2)+3u=-36 | | -7v+2(v+8)=11 | | -32=-4x+7(x-5) | | 64=10r+25 | | 2,700-150w=600 | | H(t)=t^2-8t-48 | | 6000-300x=2000 | | 4x-3/x-11=0 | | -(x-4)^2+4=0 | | 2(3×-4)=4x+3 | | 24x*42x=1/16 | | X^2+10x+28=3 | | 3(4×x)=5(10+×) | | 17×-12y=38 | | X=-17-3y | | x+x+6+6=180 | | 5x+24+13x+2+8x-3+7x+7=360 | | 4(5x-3)=7(2×+3) | | -(x-4)^(2)+4=0 | | 6(4x-1)=5x+10 | | -10x+4=36 | | -10x+4=62 | | x-2/3+x=1/4=6 | | 24=2/3(9y-15) | | 85=2x+1 | | 5/7x(x-9)=25 | | (x-5)/6=x-20 | | -7x-2(3+6x)=24-4x |

Equations solver categories